Biogas upgrading using single-walled carbon nanotubes by molecular simulation. Issue 13 (2nd November 2017) - Yang, Tingting; Lu, Linghong; Wang, Shanshan; Cao, Wei; Lu, Xiaohua
Abstract: Biogas from anaerobic digestion of biological wastes is a renewable energy resource that mainly contains CH4, CO2, trace amounts of H2 S and a fraction of H2 O vapour. In order to transfer biogas into biomethane to meet the standards for use as vehicle fuel or for injection in the natural gas grid, removing H2 S from biogas in advance is necessary. In addition, biogas is usually saturated with water vapour. It is significant to study the effect of the presence of H2 O on the biogas separation performance. Adsorption of H2 S/CO2 /CH4 and H2 O/CO2 /CH4 ternary mixtures using single-walled carbon nanotubes (SWCNT) were investigated via the Grand Canonical Monte Carlo (GCMC) method. We studied the effects of carbon nanotube diameter, –COOH modification, temperature and pressure on H2 S adsorption. The results indicate that the presence of hydrophilic –COOH groups does affect the separation of H2 S/CO2 /CH4 mixtures. Temperature swing adsorption is more suitable than pressure swing adsorption for the separation of H2 S/CO2 /CH4 mixtures. The effect of water vapour on the separation of CO2 /CH4 was also investigated. The result shows that the presence of H2 O has little effect on the selectivity of CO2 /CH4 in pristine CNT, but the selectivity of CO2 /CH4 with the presence of H2 O is markedly enhanced after modification in –COOH modified SWCNT with specific modification degree. It is expected that this work could provide some useful information for biogas upgrading.